Patient handling-related MSDs in hospital workers: analyses of 7 years Workers' Compensation claims data. (19th October 2011) - Kim, Hyun; Dropkin, Jonathan; Spaeth, Kenneth; Smith, Francine; Moline, Jacqueline
Abstract : Objectives: Musculoskeletal disorders (MSDs) are the foremost occupational injury among healthcare workers. This study investigates the magnitude of patient handling-related MSDs among employees in the largest healthcare system in New York State. Methods: MSDs were identified using reported ICD-9 codes from institutional Workers' Compensation claims (2003–09). Patient handling and other potential risk factors were obtained. Only accepted and medical cost reimbursed claims were included. Robust Poisson regression was used to evaluate determinants of patient handling-related musculoskeletal claims. Adjusted incidence rate ratios (IRR) were estimated. Results: Over 7 years, 14 WC claims were accepted per 100 full time equivalents (FTEs) (3452 claims/24824 FTEs). Sixty-seven percent of these claims were diagnosed as MSDs (n=2312). Patient handling-related MSDs accounted for 41% (n=940). Among patient handling-related MSDs, workers employed under 5 years at the health system had over three times more claims than workers employed over 20 years (IRR=3.1 (2.5–3.7)), while men experienced slightly higher claims than women (IRR=1.2 (1.1–1.4)), and emergency medical technicians (EMTs) had two time more claims than nurses. Union membership, shift schedule, and full-time status showed no significant relationship; some effects were shown in evening shift (IRR=1.1 (1.0–1.3) and per-diem (IRR=1.3 (1.0–1.5)). Forty two percent of injuries occurred while lifting patients and 19% occurred while holding or carrying patients. EMTs obtained 85% of MSDs from patient lifting, holding, or carrying. Lifting, holding or carrying patients explained over half of patient handling-related MSDs. Conclusions: The above risk factors can be modified through proper engineering controls.